Thermodynamic and thermoeconomic analyses of the energy segmented stepped utilization of medium- and low-temperature steam based on a dual-stage organic Rankine cycle. (25th January 2023) - Zhang, Hongsheng; Liu, Xingang; Hao, Ruijun; Ba, Xiaobin; Liu, Chengjun; Liu, Yifeng; Duan, Chenghong; Qiao, Manman; Qin, Jiyun
Highlights: Proposed a novel method of energy segmented stepped utilization focusing on steam. Constructed a dual-stage ORC based on heat release characteristic of heat source. Established thermoeconomic model in terms of energy, exergy and economic methods. Revealed performance and economy change from qualitative and quantitative perspective. Abstract: A novel method of energy segmented stepped utilization is proposed on the basis of temperature evolution characteristics in steam energy release process in this paper. A dual-stage organic Rankine cycle (DORC) coupled by a non-azeotropic ORC (namely, high-temperature ORC, HT-ORC) and a pure working medium ORC (namely, low-temperature ORC, LT-ORC) is constructed, in which the HT-ORC and LT-ORC are employed as the energy receiving sides of the variable temperature and constant temperature exothermic sections in the steam energy release process, respectively. Due to the characteristics of temperature slip of non-azeotropic ORC and constant temperature evaporation of pure working medium ORC, the heat absorption line of organic working medium and heat release line of steam are more parallel to reduce irreversible loss of heat transfer in the variable temperature and constant temperature exothermic sections in the steam energy release process, so as to improve the effective energy input of heat source. It is found that the net output power, thermal and exergy efficiencies of DORC-R141b are 287.82 kW, 12.27 % and 53.57 %, respectively, as the mass fraction of R141b is 0.20 and LT-ORC evaporation temperature is 90 ℃. Compared with the conventional integral utilization model of steam energy (namely, single-stage organic Rankine cycle, SORC), the net output power, thermal and exergy efficiencies are enhanced by 15.95 kW, 0.68 % and 2.97 % in the DORC-R141b. The effective energy input is increased by 5.89 % and total exergy loss is reduced by 19.58 kW. Moreover, the levelized costs of electricity (LCOE) of DORC-R141b and SORC-R245fa/R141b are 0.0570 /kWh and 0.0558 /kWh, the net present value (NPV) are 296, 550 /year and 306, 680 /year, the dynamic payback periods (DPP) are 4.36 years and 3.20 years, the multiple of investment costs (MOIC) are 2.78 and 3.63, respectively. In addition, the CO2 emission can be reduced by 315.18 tons per year after adopting energy segmented stepped utilization of the steam energy. The results show that the energy segmented stepped utilization mode not only has significant advantages in both thermodynamic performance and environmental protection, but also is economically feasible, which has broad application potential for the efficient utilization of medium- and low-temperature steam in industry.